Developing parental psychological competencies by means of online training - V. Vardanyan, Yulia (2021)
The purpose of this paper is to substantiate the successful methods for developing psychological competencies in parents against the backdrop of a global pandemic based on online technologies. The leading research method consisted in integration of the online training resources, which has provided a comprehensive view of diagnostics into the personal characteristics of students’ parents preventing them from successful resolution of problems within the family complemented with the fostering of psychological parental competencies. This paper presents the analysis of materials collected in the course of online diagnostics of problems related to implementation of psychological parental competencies. In conclusion, it presented an overview of the development program “Family Kaleidoscope”, provided evidence of its high impact on the adoption of the productive parenting style. The paper findings may be useful for the already practicing and future educational psychologists striving to improve interactions within the students’ families for creating a favorable environment for successful socialization of children.